2018
DOI: 10.1083/jcb.201703196
|View full text |Cite
|
Sign up to set email alerts
|

Actin polymerization controls cilia-mediated signaling

Abstract: Primary cilia are polarized organelles that allow detection of extracellular signals such as Hedgehog (Hh). How the cytoskeleton supporting the cilium generates and maintains a structure that finely tunes cellular response remains unclear. Here, we find that regulation of actin polymerization controls primary cilia and Hh signaling. Disrupting actin polymerization, or knockdown of N-WASp/Arp3, increases ciliation frequency, axoneme length, and Hh signaling. Cdc42, a potent actin regulator, recruits both atypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 45 publications
3
70
0
Order By: Relevance
“…We showed that cilia elongation in OSNs of Joubert model validates importance of INPP5E to the cilia maintenance. However, as pointed earlier redistribution of PIP2 may induce aberrant remodeling of ciliary core by recruiting F-actin filaments thus contributing to cilia elongation (Madhivanan et al, 2015;Phua et al, 2017;Drummond et al, 2018). Ciliopathy associated with altered PIP2 distribution is not limited only by Joubert (INPP5E) syndrome but also occurs in a similar disease of oculo-cerebro-renal syndrome of Lowe (OCRL).…”
Section: Discussionmentioning
confidence: 91%
“…We showed that cilia elongation in OSNs of Joubert model validates importance of INPP5E to the cilia maintenance. However, as pointed earlier redistribution of PIP2 may induce aberrant remodeling of ciliary core by recruiting F-actin filaments thus contributing to cilia elongation (Madhivanan et al, 2015;Phua et al, 2017;Drummond et al, 2018). Ciliopathy associated with altered PIP2 distribution is not limited only by Joubert (INPP5E) syndrome but also occurs in a similar disease of oculo-cerebro-renal syndrome of Lowe (OCRL).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, adhesion complexes such as those in focal adhesions are found in basal bodies, thus linking cilia with the actin cytoskeleton (Antoniades et al, 2014). Actin polymerization indeed affects primary cilium length and function (Kim et al, 2015;Drummond et al, 2018). Thus, a putative function of TRIP6 in ciliogenesis via a regulation of the actin cytoskeleton cannot be ruled out at this time.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that loss of aPKC increased ciliogenesis and axoneme length, while suppressing HH pathway activation (Atwood et al 2013;Drummond et al 2018), suggesting that aPKC expression may dynamically regulate ciliogenesis. To further define the association between ciliogenesis and aPKC expression, we examined primary cilia upon aPKC overexpression.…”
Section: Apkc and Primary Cilia Mutually Inhibit Each Othermentioning
confidence: 99%
“…In this study, we find that loss of highly mutated cilia-associated genes disrupts primary cilia and attenuates HH pathway activation. Loss of primary cilia results in higher aPKC expression, which normally serves to restrict ciliogenesis (Drummond et al 2018). Expression of an aPKC isoform that only contains the kinase domain promotes HH signaling in the presence or absence of primary cilia and can confer resistance to vismodegib.…”
Section: Introductionmentioning
confidence: 99%